The making of another major motion picture masterpiece (Alfred A. Knopf, Books on Tape, Random House Audio, 2023)
"From the Academy Award-winning actor and best-selling author: his debut novel. The story of the making of a colossal, star-studded, multimillion-dollar superhero action film...and the humble comic book that inspired it. PART ONE of this story takes place in 1947. A troubled soldier, returning from the war, meets his talented five-year-old nephew, leaves an indelible impression, and then disappears for 23 years. Cut to 1970: The nephew, now drawing underground comic books in Oakland, California, reconnects with his uncle and, remembering the comic book he saw when he was five, draws a new version with his uncle as a World War II fighting hero. Cut to the present day: A commercially successful director discovers the 1970 comic book and decides to turn it into a contemporary superhero movie. Cue the cast: We meet the film's extremely difficult male star, his wonderful leading lady, the eccentric writer/director, the producer, the go-fer production assistant, and everyone else on both sides of the camera. Funny, touching, and wonderfully thought-provoking, this is a novel not only about the making of a movie, but also about the changes in America and American culture since World War II. Bonus material: Interspersed throughout are the three comic books that are featured in the story - all created by Hanks himself - including the comic book that becomes the official tie-in to this novel's "major motion picture masterpiece.""--
Back story , Source material , Development hell , Prep , Casting , The shoot , Post.